Kajian Kebolehgunaan E-Gamifikasi Minecraft Bagi Kursus Falsafah Islam - Kamal Azmi Abd Rahman; Nik Mohamad Firdaus Hilmi Ab Wahab; Nur Syahifa Nadhirah Mohd Khairi; Muhammad Tarmidzi Ibrahim; Mohd Azfar Abdul Malik; Siti Khadijah Azairi (Universiti Islam Melaka, 2026)
Tier 3- Indexed by MyCite